Anaerobic re‐digestion of digested sludge post‐treated by ultrasound: effect of the adding linear alkylbenzene sulfonate. Issue 8 (25th March 2018) - Shao, Liming; Li, Wenpeng; Lü, Fan; He, Pinjing
Abstract: BACKGROUND: Increasing the degradation ratio of organic matter is one of the key challenges for sludge anaerobic digestion. The conventional solution is by directly treating the raw sludge so as to enhance the sludge degradation. In contrast, the target of the present study was digested sludge enriching in refractory organic matter. The method proposed to improve the organic degradation of digested sludge uses ultrasound combined with linear alkylbenzene sulfonate (LAS) to control flocs re‐flocculation. RESULTS: Gas production of the sludge treated with the highest ultrasound energy (360 W, 20 min) was only 57.7 ± 0.3 mL‐CH4 g ‐1 ‐VSadded, and the sludge treated with lower ultrasound energy (120 W, 20 min) with LAS had the highest gas production, up to 92.5 ± 8.5 mL‐CH4 g ‐1 ‐VSadded . Meanwhile, the total VS degradation of 120 W, 20 min with LAS was up to 69.6 ± 5.2%. And the gas production of 360 W, 5 min with LAS was 27.1% higher than that of 360 W, 5 min without LAS. CONCLUSION: These results revealed that digested sludge treated by ultrasonication could be further degraded, and the addition of LAS could significantly improve the re‐digestion performance with less energy. © 2018 Society of Chemical Industry